High-efficiency heat-conducting lead-free solder paste and preparation method thereof

By adopting optimized flux formulation and tin alloy particle size in solder paste, the problems of reduced thermal conductivity and poor solder quality in high temperature environments are solved, and the efficient thermal conductivity and welding quality are improved.

CN119820171AActive Publication Date: 2025-04-15GUANGDONG GAOHAILIANG TECHNOLOGY IND CO LTD

Patent Information

Application Number
CN202510237152.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-01
Publication Date
2025-04-15
Estimated Expiration
2045-03-01

AI Technical Summary

Technical Problem

Traditional solder paste is prone to forming bubbles and holes in high temperature environments, resulting in reduced thermal conductivity and poor soldering quality, especially in high-power electronic equipment such as inverter modules of new energy vehicles.

Method used

High-efficiency thermally conductive lead-free solder paste composed of tin alloy and flux, which consists of rosin derivatives, active agents, liquid polyisobutylene, maleic anhydride-containing copolymer, etc. The flux content is controlled at 15-25% of the weight of the tin alloy to achieve full dispersion of the tin alloy and the fullness of the solder joints.

Benefits of technology

By optimizing the flux formulation and tin alloy particle size, the thermal conductivity efficiency and stability of solder joints are significantly improved after welding, the occurrence of hollowing is reduced, and the welding quality and adhesion stability of solder joints are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005293031960000071
    Figure BDA0005293031960000071
  • Figure BDA0005293031960000081
    Figure BDA0005293031960000081
  • Figure BDA0005293031960000091
    Figure BDA0005293031960000091
Patent Text Reader

Abstract

The invention relates to the field of electronic packaging materials, in particular to efficient heat-conducting lead-free solder paste and a preparation method thereof. The tin alloy is composed of tin alloy and scaling powder, and the weight of the scaling powder accounts for 15-25% of the weight of the tin alloy. The soldering flux is prepared from the following raw materials in percentage by weight: 42 to 60 percent of rosin derivative, 5 to 10 percent of active agent, 5 to 10 percent of liquid polyisobutene, 2.5 to 5.5 percent of maleic anhydride-containing copolymer, 1 to 3 percent of ethylene bisstearamide, 1 to 3 percent of hydrogenated castor oil and the balance of solvent. The rosin derivative, the liquid polyisobutene, the maleic anhydride-containing copolymer and other raw materials play a synergistic role, so that the obtained soldering paste has better flowability, wettability, film-forming property and the like, the dispersion uniformity of a soldering flux and tin alloy powder is improved, a small amount of the soldering flux volatilizes in a welding spot in the welding process, the possibility of holes is avoided, and the service life of the soldering paste is prolonged. And the heat conduction efficiency and the stability of a welding spot after welding are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic packaging materials, and in particular to a highly efficient thermally conductive lead-free solder paste and a preparation method thereof. Background Art

[0002] Solder paste is widely used in the electronics manufacturing industry, especially in semiconductor packaging and circuit board assembly. As electronic products develop towards miniaturization and high performance, the requirements for solder paste are getting higher and higher. Traditional solder paste is mainly composed of tin alloy powder and flux, where the function of flux is to remove oxides on the metal surface and promote good bonding between solder and metal surface. However, with the diversification of application scenarios and the improvement of technical requirements, traditional solder paste has gradually exposed its shortcomings in certain specific applications. For example, in high-power electronic devices, especially inverter modules in new energy vehicles, their core components IGBT (insulated gate bipolar transistor) will generate a lot of heat during operation, and efficient heat dissipation measures are required to ensure its normal operation.

[0003] In order to meet this challenge, the existing technology has proposed a variety of solutions. Common methods include using solder materials with better thermal conductivity and optimizing the flux formula to improve welding quality and heat dissipation efficiency. However, after soldering, the solder paste is prone to voids, thereby reducing thermal conductivity. Especially in high temperature environments, the existing solder paste is prone to form bubbles due to excessive volatile components in the flux, resulting in holes inside the solder joint, which in turn affects the heat dissipation efficiency and welding quality. These problems limit the performance of the existing technology in practical applications, and it is urgent to develop a highly efficient thermal conductive lead-free solder paste to overcome the above defects. Summary of the invention

[0004] The present invention reduces the cavitation phenomenon of solder paste after welding, while ensuring the stability after welding, and provides a highly efficient thermal conductive lead-free solder paste and preparation method thereof. A highly efficient thermally conductive lead-free solder paste, comprising a tin alloy and a soldering flux, wherein the soldering flux is 15-25% by weight of the tin alloy; the soldering flux is composed of the following raw materials in the following weight percentages: Rosin derivatives 42-60% Active agent 5-10% Liquid polyisobutylene 5-10% Copolymer containing maleic anhydride 2.5-5.5% Ethylene bisstearamide 1-3% Hydrogenated castor oil 1-3% The balance is solvent.

[0005] By adopting the above technical solution, the high-efficiency thermal conductive lead-free solder paste has the following effects: First of all, the flux content of the present application is low, which can achieve full and uniform dispersion of tin alloy, so that the solder paste has better fluidity, wettability and film-forming property, avoids the possibility of voids after welding, and improves welding quality and thermal conductivity. The proportion of rosin derivatives is high, and it works synergistically with the copolymer component containing maleic anhydride to further improve adhesion and thermal stability, and ensure reliability during welding. The addition of liquid polyisobutylene significantly enhances the wettability and thermal stability of the solder paste, ensures that the solder joints are full during welding, reduces the void rate, and the liquid polyisobutylene works synergistically with the copolymer containing maleic anhydride. The copolymer containing maleic anhydride improves the film-forming property and chemical stability of the flux, effectively prevents oxidation and corrosion of the metal surface during welding, and optimizes the quality of the welded joint. Ethylene bisstearamide and hydrogenated castor oil work together to improve the handling performance of the solder paste, reduce volatilization losses at high temperatures, and improve the consistency and thermal conductivity of the final solder joints.

[0006] In summary, the present application utilizes a relatively low content of flux to achieve full and uniform dispersion of the tin alloy, and uses rosin derivatives, activators, liquid polyisobutylene, copolymers containing maleic anhydride and other raw materials to enhance the synergy, so that the obtained solder paste has better fluidity, wettability and film-forming properties, etc. During the welding process, a small amount of flux evaporates in the solder joint, avoiding the possibility of holes, thereby improving the welding quality, the thermal conductivity of the solder joint after welding, and the stability of the solder joint.

[0007] When a lower content of flux is used, it is difficult to fully mix with the tin alloy powder, and during welding, the wettability and diffusivity are low, resulting in incomplete solder joints and a high void rate.

[0008] Preferably, the chemical elements of the tin alloy consist of 85-93wt% tin, 2-6wt% silver, 1-5wt% copper, 0.1-3% boron, and 0.5-2.5% silicon.

[0009] The above raw material composition and usage ratio are all within the preferred range of the present application, and the obtained tin alloy has better comprehensive properties such as thermal conductivity, corrosion resistance, and easy dispersion, and can be evenly mixed with the flux of the present application to reduce the occurrence of voids after welding.

[0010] Preferably, the particle size of the tin alloy is 20-38 μm.

[0011] By adopting the above technical solution, the particle size of the tin alloy is controlled within the range of 20-38μm, so that the solder paste can better fill the gap between the chip and the motherboard during the soldering process, increasing the contact area while reducing the void rate. This optimization brings the following effects: First, the evenly distributed tin particles improve the fullness of the solder joints and reduce the risk of reduced thermal conductivity due to bubbles; second, the moderate particle size range takes into account the fluidity and stability of the solder paste, ensuring good operability and high heat dissipation efficiency during the soldering process.

[0012] Preferably, the rosin derivative is composed of at least three of hydrogenated rosin methyl ester, rosin-modified phenolic resin, rosin-modified maleic acid resin, and water-white rosin resin.

[0013] By adopting the above technical solution, the rosin derivative is composed of at least three of hydrogenated rosin methyl ester, rosin modified phenolic resin, rosin modified maleic acid resin, and water-white rosin resin, which can significantly improve the comprehensive performance of the flux. Specifically: The combined use of multiple rosin derivatives enhances the adhesion and film-forming properties of the flux, helps to form a more uniform and dense protective film, and improves the quality and reliability of the soldering joint. Different types of rosin derivatives work together to improve the stability of the flux at high temperatures, reduce the performance degradation caused by temperature fluctuations, and ensure the smooth progress of the soldering process. The synergistic effect of multiple rosin derivatives improves the wettability of the flux, making it easier for the solder to be evenly distributed throughout the soldering area, improving the coverage and uniformity of the soldering. Different rosin derivatives have different degrees of antioxidant capacity, and their combined use can effectively prevent the metal surface from oxidizing during the soldering process and protect the quality of the soldering joint.

[0014] In summary, the combination of various rosin derivatives, liquid polyisobutylene, and copolymers containing maleic anhydride are used to further improve the wetting, dispersibility, film-forming, and adhesion of the flux, so that it can be fully mixed with the tin alloy, so that the obtained solder paste has a better welding effect during welding, and can also reduce the generation of voids after welding and improve the thermal conductivity. After welding, the bonding is stable to avoid the possibility of falling off.

[0015] Preferably, the active agent is one or more of decyltetradecanoic acid, 1-hydroxybenzotriazole monohydrate, trimethylbutenediol, succinic acid, and tartaric acid.

[0016] By adopting the above technical solution, the activator is selected from one or more combinations of decyl tetradecanoic acid, 1-hydroxybenzotriazole monohydrate, trimethylbutylene glycol, succinic acid or tartaric acid, which can significantly improve the activation performance of the flux. These organic acid activators can not only effectively remove oxides on the metal surface, but also enhance the wettability and adhesion of the solder joints, thereby improving the welding quality and reliability. In addition, this selection also takes into account environmental protection and lead-free requirements, further improving the overall performance of the solder paste.

[0017] Preferably, the liquid polyisobutylene is polyisobutylene 300R.

[0018] By adopting the above technical solution, the liquid polyisobutylene is selected from polyisobutylene 300R, whose good wettability and thermal stability significantly improve the soldering performance of the solder paste. It also plays a synergistic role with the copolymer containing maleic anhydride to further improve the comprehensive performance of the solder.

[0019] Preferably, the maleic anhydride-containing copolymer is methyl vinyl ether-maleic anhydride copolymer.

[0020] By adopting the above technical solution, the use of methyl vinyl ether-maleic anhydride copolymer significantly improves the film-forming property, wettability and thermal stability of the flux. It also plays a synergistic role with polyisobutylene 300R to further improve the comprehensive performance of the flux, so that the solder paste obtained after soldering has a reduced possibility of voids and has better adhesion stability.

[0021] Specifically, film-forming property: methyl vinyl ether-maleic anhydride copolymer forms a uniform and dense film on the metal surface, which effectively prevents the metal from being oxidized and corroded during the welding process and protects the quality of the welded joint.

[0022] Wettability: The copolymer improves the fluidity of the flux, allowing it to better wet the metal surface, helping the solder to be more evenly distributed on the metal joint, improving the reliability and quality of soldering.

[0023] Thermal stability: Methyl vinyl ether-maleic anhydride copolymer has excellent chemical stability and thermal stability, and can withstand high temperatures and chemical reactions during welding, ensuring that the flux maintains stable performance during welding, reducing the volatilization and decomposition of the flux, thereby improving welding quality and the thermal conductivity of solder joints.

[0024] Preferably, the ethylene bisstearic acid amide is ethylene bis(12-hydroxy)stearic acid amide and / or ethylene bis(16-hydroxy)stearic acid amide.

[0025] By adopting the above technical solution, ethylene bis(12-hydroxy) stearic acid amide and / or ethylene bis(16-hydroxy) stearic acid amide are specifically selected as ethylene bisstearic acid amide, which can significantly improve the lubricity and thermal stability of the flux.

[0026] In summary, the selection of ethylene bis(12-hydroxy) stearamide and / or ethylene bis(16-hydroxy) stearamide as the specific components of ethylene bis(stearamide) not only improves the comprehensive performance of the flux, but also further improves the saturation and thermal conductivity of the solder joint and reduces the occurrence of voids.

[0027] Preferably, the maleic anhydride-containing copolymer is prepared from the following raw materials in weight percentage: Contains 3-5% acrylate-based diluent Methacryloyloxypropyl di-terminated polydimethylsiloxane 5-10% Maleic anhydride 2-5% Initiator 0.02-0.05% The balance was methyl vinyl ether-maleic anhydride copolymer.

[0028] Methacryloyloxypropyl double-terminated polydimethylsiloxane, acrylate-based diluent, and maleic anhydride can undergo a copolymerization reaction under the action of an initiator to generate a copolymer with better film-forming properties, wettability, and thermal stability, and the copolymer can synergize with a methyl vinyl ether-maleic anhydride copolymer. The obtained copolymer containing maleic anhydride is used in a soldering flux, which can further improve the comprehensive performance of the soldering flux, reduce the phenomenon of lead voids in the solder paste after soldering, stabilize adhesion on a PBC board, and improve the thermal conductivity of the solder paste after application.

[0029] In a second aspect, a method for preparing a highly efficient thermally conductive lead-free solder paste is prepared by the following method: According to weight percentage, rosin derivative, activator, liquid polyisobutylene, copolymer containing maleic anhydride, ethylene bisstearic acid amide, hydrogenated castor oil, and solvent are weighed and mixed evenly to obtain a soldering flux; According to weight percentage, soldering flux and tin alloy are weighed and mixed evenly to obtain solder paste.

[0030] By adopting the above technical solution, the highly efficient thermal conductive lead-free solder paste prepared has the following effects: Optimization of soldering flux: The ratio of soldering flux components is reasonable. The synergistic effect of rosin derivatives, activators, liquid polyisobutylene, copolymers containing maleic anhydride and other ingredients improves the film-forming property, wettability and thermal stability of soldering flux. In particular, the combination of liquid polyisobutylene and methyl vinyl ether-maleic anhydride copolymer enhances wettability and thermal stability, ensures uniform distribution of solder during soldering, reduces voids, and improves soldering quality and thermal conductivity.

[0031] Tin alloy optimization: The chemical element composition and particle size range of tin alloy are precisely controlled to ensure high thermal conductivity and good welding performance of tin alloy. The presence of silver, copper, boron, silicon and other elements in tin alloy not only improves the melting point and mechanical strength, but also enhances the corrosion resistance and oxidation resistance of solder joints.

[0032] Improved overall performance: Through a reasonable ratio of flux and tin alloy, the final lead-free solder paste has high thermal conductivity, good fluidity and wettability, while reducing volatilization and voids during the welding process, significantly improving the thermal conductivity and reliability after welding.

[0033] Simple process: The preparation method is simple and easy. The preparation of flux and solder paste can be completed by weighing each component and mixing them evenly, which is convenient for large-scale production and application.

[0034] In summary, the present application includes at least one of the following beneficial technical effects: 1. By adopting a lower flux content and optimizing the formula design, the tin alloy components are fully and evenly dispersed, forming a welding effect with full solder joints and low porosity, which significantly improves the thermal conductivity and heat dissipation efficiency; the rosin derivatives and the copolymers containing maleic anhydride work synergistically to enhance the film-forming and adhesion properties of the flux and improve the stability of the solder joints in high temperature environments; liquid polyisobutylene and the copolymers containing maleic anhydride jointly improve the wettability of the flux, promote the effective combination of solder and metal surface, and further ensure the welding quality.

[0035] 2. Methacryloyloxypropyl double-terminated polydimethylsiloxane, acrylate-based diluent, and maleic anhydride can undergo copolymerization under the action of an initiator to generate a copolymer with better film-forming properties, wettability, and thermal stability, and synergistically react with methyl vinyl ether-maleic anhydride copolymer. The obtained copolymer containing maleic anhydride is used in flux, which can further improve the comprehensive performance of the flux, reduce the phenomenon of wire voids in the solder paste after welding, and maintain stable adhesion on the PBC board, thereby improving the thermal conductivity of the solder paste after application. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments.

[0037] Liquid polyisobutylene is polyisobutylene 300R, Japanese Idemitsu polyisobutylene 300R; Hydrogenated castor oil Jiangsu Minglin Chemical Technology Co., Ltd. EL-40 Hydrogenated rosin methyl ester CAS: 8050-15-5; Rosin modified phenolic resin Sanming Senke New Materials Co., Ltd. F-2136 Rosin modified maleic acid resin Deqing County Haizhuo Chemical Co., Ltd. ML-103; Water-white rosin resin Komao KA100W; Methyl vinyl ether-maleic anhydride copolymer CAS No. 9011-16-9 Methacryloyloxypropyl di-terminated polydimethylsiloxane has a molecular weight of 8000-10000; CAS number 58130-03-3.

[0038] Preparation Example of Copolymer Containing Maleic Anhydride Preparation Example 1 A copolymer containing maleic anhydride is prepared by the following method: According to the weight percentage, 5% of methacryloyloxypropyl dicapped polydimethylsiloxane, 2% of maleic anhydride, 5% of acrylate-based diluent, and 0.05% of initiator were weighed and mixed evenly, heated to 60°C, reacted for 2 hours, and then 87.95% of methyl vinyl ether-maleic anhydride copolymer was added and mixed evenly to obtain a copolymer containing maleic anhydride. Among them, the initiator is dibenzoyl peroxide initiator, and the acrylate-based diluent is dipropylene glycol diacrylate.

[0039] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the amount of raw materials used is different, specifically: according to weight percentage, 7% methacryloyloxypropyl di-terminated polydimethylsiloxane, 3% maleic anhydride, 4% acrylate-based diluent, 0.03% initiator, and 85.97% methyl vinyl ether-maleic anhydride copolymer are weighed.

[0040] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the amount of raw materials used is different, specifically: according to weight percentage, 10% methacryloyloxypropyl di-terminated polydimethylsiloxane, 2% maleic anhydride, 3% acrylate-based diluent, 0.02% initiator, and 84.92% methyl vinyl ether-maleic anhydride copolymer are weighed.

[0041] Preparation Comparative Example Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of methacryloyloxypropyl di-terminated polydimethylsiloxane is replaced by maleic anhydride. Example

[0042] Example 1 A method for preparing a highly efficient thermally conductive lead-free solder paste comprises the following steps: According to weight percentage, 42% of rosin derivatives, 5% of active agents, 10% of liquid polyisobutylene, 5.5% of copolymers containing maleic anhydride, 3% of ethylene bisstearic acid amide, 3% of hydrogenated castor oil, and 31.5% of solvents are weighed and mixed evenly to obtain a soldering flux, wherein the rosin derivatives are composed of hydrogenated rosin methyl ester, hydrogenated rosin methyl ester, and water-white rosin resin in a weight ratio of 1:1:3; the active agent is decyl tetradecanoic acid; the solvent is diethylene glycol monohexyl ether, the liquid polyisobutylene is polyisobutylene 300R; the ethylene bisstearic acid amide is ethylene bis(12-hydroxy)stearic acid amide; and the copolymer containing maleic anhydride is methyl vinyl ether-maleic anhydride copolymer.

[0043] According to weight percentage, soldering flux and tin alloy are weighed and mixed evenly, with the soldering flux accounting for 15% of the weight of the tin alloy, to obtain solder paste.

[0044] The particle size of the tin alloy may be 20-38 μm, and in this embodiment, preferably 25 μm.

[0045] In terms of weight percentage, the chemical elements of the tin alloy are composed of 85wt% tin, 6wt% silver, 5wt% copper, 3% boron, and 1% silicon.

[0046] Example 2 The difference between Example 2 and Example 1 is that the soldering flux is 21% of the weight of the tin alloy; in terms of weight percentage, the chemical elements of the tin alloy are composed of 89wt% tin, 5wt% silver, 3wt% copper, 2% boron, and 1% silicon.

[0047] Example 3 The difference between Example 3 and Example 1 is that the soldering flux is 25% of the weight of the tin alloy; in terms of weight percentage, the chemical elements of the tin alloy are composed of 93wt% tin, 2wt% silver, 1wt% copper, 3% boron, and 1% silicon.

[0048] Example 4 The difference between Example 4 and Example 2 is that the rosin derivative consists of rosin-modified phenolic resin, rosin-modified maleic acid resin, and hydrogenated rosin methyl ester in a weight ratio of 1:1:3.

[0049] Example 5 The difference between Example 5 and Example 2 is that the active agent is composed of decyltetradecanoic acid and succinic acid in a weight ratio of 1:1.

[0050] Example 6 The difference between Example 6 and Example 2 is that ethylene bisstearic acid amide is composed of ethylene bis(12-hydroxy)stearic acid amide and ethylene bis(16-hydroxy)stearic acid in a weight ratio of 1:1.

[0051] Embodiment 7-8 The difference between Example 7-8 and Example 2 is that the raw material composition of the soldering flux is different, as shown in Table 1; Table 1 Raw material composition of the soldering flux of Example 2, Example 7-8 (%) Example 9 The difference between Example 9 and Example 7 is that the source of the copolymer containing maleic anhydride is Preparation Example 1.

[0052] Example 10 The difference between Example 10 and Example 7 is that the source of the copolymer containing maleic anhydride is Preparation Example 2.

[0053] Embodiment 11 The difference between Example 11 and Example 7 is that the source of the copolymer containing maleic anhydride is Preparation Example 3.

[0054] Example 12 The difference between Example 12 and Example 7 is that the source of the copolymer containing maleic anhydride is Preparation Comparative Example 1.

[0055] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the liquid polyisobutylene is replaced by an equal amount of a copolymer containing maleic anhydride.

[0056] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the copolymer containing maleic anhydride is replaced by liquid polyisobutylene in equal amount.

[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the liquid polyisobutylene and the copolymer containing maleic anhydride are replaced by rosin in equal amounts.

[0058] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the soldering flux is 40% of the weight of the tin alloy.

[0059] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the soldering flux is 8% by weight of the tin alloy.

[0060] Performance testing The solder pastes obtained in Examples 1-12 and Comparative Examples 1-5 were soldered on PCB boards at 200° C. to form solder joints, and then the following tests were performed.

[0061] Detection method / test method (1) Void test: The void ratio of solder joints formed by soldering of Examples 1-12 and Comparative Examples 1-5 was measured by microscopic observation of sections. The judgment criteria were as follows: the soldering condition after sectioning was observed using an electron metallographic microscope. The void ratio did not exceed 20% of the solder ball area. Intermetallic was formed. There was no void crack.

[0062] Table 2 IPC void standards for BGA: IPC 7095 7.4.1.6 1. Quality inspection Table 3 Quality inspection (3) Adhesion: Test conditions based on JIS-Z-3284 standard; Test equipment: Adhesion tester; Pressing speed: 2.0 mm / s; Pressing time: 0.2 s; Measurement load: 0.49 N; Lifting speed: 10.0mm / s; Test environment: 25℃, 50%RH; Table 4 Experimental data of Examples 1-12 and Comparative Examples 1-5 Combining Example 1 and Comparative Examples 1-5 and Table 4, it can be seen that the quality of Comparative Examples 1-3 is unqualified and the void rate is high, indicating that the present application can achieve full and uniform dispersion of the tin alloy by using a lower content of flux, and the rosin derivative, liquid polyisobutylene, and copolymer containing maleic anhydride of the present application are compounded to play a synergistic role, which can reduce a small amount of volatilization in the solder joint during the welding process, avoid the possibility of holes, and improve the welding quality, the thermal conductivity of the solder joint after welding, and the stability of the solder joint.

[0063] Combining Example 9 with Example 7 and Table 4, it can be seen that the adhesion of Example 9 is higher than that of Example 7, while the void rate is lower than that of Example 7, indicating that the copolymer containing maleic anhydride prepared by using methacryloyloxypropyl di-terminated polydimethylsiloxane, maleic anhydride, acrylate-based diluent, and methyl vinyl ether-maleic anhydride copolymer is used in the flux to further improve the comprehensive performance, and other physical interactions are achieved to improve the adhesion stability of the solder paste after welding, reduce the generation of void rate, and improve its thermal conductivity.

[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly efficient thermally conductive lead-free solder paste, characterized in that: It is composed of tin alloy and flux, the flux is 15-25% of the weight of the tin alloy; the flux is composed of the following raw materials in weight percentage: Rosin derivatives 42-60% Active agent 5-10% Liquid polyisobutylene 5-10% Copolymer containing maleic anhydride 2.5-5.5% Ethylene bisstearamide 1-3% Hydrogenated castor oil 1-3% The balance is solvent.

2. The highly efficient thermally conductive lead-free solder paste according to claim 1, characterized in that: The chemical elements of the tin alloy are composed of 85-93wt% tin, 2-6wt% silver, 1-5wt% copper, 0.1-3% boron, and 0.5-2.5% silicon.

3. The highly efficient thermally conductive lead-free solder paste according to claim 1, characterized in that: The particle size of the tin alloy is 20-38 μm.

4. The highly efficient thermally conductive lead-free solder paste according to claim 1, characterized in that: The rosin derivatives are composed of at least three of hydrogenated rosin methyl ester, rosin-modified phenolic resin, rosin-modified maleic acid resin and water-white rosin resin.

5. The highly efficient thermally conductive lead-free solder paste according to claim 1, characterized in that: The active agent is one or more of decyl tetradecanoic acid, 1-hydroxybenzotriazole monohydrate, trimethylbutylene glycol, succinic acid and tartaric acid.

6. The highly efficient thermally conductive lead-free solder paste according to claim 1, characterized in that: The liquid polyisobutylene is polyisobutylene 300R.

7. The high-efficiency thermally conductive lead-free solder paste according to claim 1, characterized in that: The maleic anhydride-containing copolymer is a methyl vinyl ether-maleic anhydride copolymer.

8. The high-efficiency thermally conductive lead-free solder paste according to claim 1, characterized in that: The ethylene bis stearic acid amide is ethylene bis (12-hydroxy) stearic acid amide and / or ethylene bis (16-hydroxy) stearic acid amide.

9. The highly efficient thermally conductive lead-free solder paste according to claim 1, characterized in that: The maleic anhydride-containing copolymer is prepared from the following raw materials in weight percentage: Contains 3-5% acrylate-based diluent Methacryloyloxypropyl di-terminated polydimethylsiloxane 5-10% Maleic anhydride 2-5% Initiator 0.02-0.05% The balance was methyl vinyl ether-maleic anhydride copolymer.

10. A method for preparing a high-efficiency thermally conductive lead-free solder paste according to any one of claims 1 to 9, characterized in that: Prepared by the following method: According to weight percentage, rosin derivative, activator, liquid polyisobutylene, copolymer containing maleic anhydride, ethylene bisstearic acid amide, hydrogenated castor oil, and solvent are weighed and mixed evenly to obtain a soldering flux; According to weight percentage, soldering flux and tin alloy are weighed and mixed evenly to obtain solder paste.

Citation Information

Patent Citations

  • Precision welding lead-free solder paste with low voidage and preparation method thereof

    CN118720518A

  • Flux composition for soldering

    JP1991081092A

  • Soldering flux

    JP2009248114A

  • Curable flux composition and solder paste comprising the same

    KR1020160010683A

  • Sintering composition, sintered body, and bonded structure

    WO2022065418A1

Cited By

  • Halogen-free soldering flux for solder paste and preparation method of halogen-free soldering flux

    CN120155692A